Development of Foundation Formulation From Eggshells as Anti UV Agent - Putri, Salsa Davincy; Mardhiani, Yanni Dhiani; Adiyati Rum, Ira (Universitas Padjadjaran (Unpad), 2024)
Foundation often contains anti-UV filters whether synthetic or natural. One of the natural ingredients that can be used as an anti-UV agent is eggshells because they contain calcium carbonate. This study aim to develop foundation as cosmetic preparation containing of duck eggshells and Moringa seed oil (Moringa oleifera Lam.) for anti-UV agent. The combination of duck eggshell and moringa seed oil is carried out with the hypothesis can increase the ability of the preparation to protect the skin from exposure to solar radiation. Foundation preparation were made in 6 formulas with varying concentrations of duck eggshells and moringa seed oil. Evaluation of the preparations carried out included organoleptic test, homogeneity, pH, viscosity, spreadability, and color dispersion for 28 days at room temperature, freeze thaw stability test for 6 cycles, and anti-UV activity were carried out using spectrophotometry UV-Vis. The results of the evaluation were analyzed using One-Way ANOVA method. Based on the results of physical evaluation analysis, all formulas showed stable foundation preparations. All preparations showed a non-irritative category after an irritation test on test animals (albino rabbits). Anti-UV activity with an average SPF value for F0 was 4,2±0,29 (minimal category), F1 was 18.75±1.41 (ultra category), F2 13.68±0.73 (maximum category), F3 14.00±0.46 (maximum category), F413.02±0.47 (maximum category), and F5 18.14±0.31 (ultra category). Keywords: Eggshells, moringa seed oil, cosmetic foundation, SPF